Effect of Different Seed Rates on Oil and Protein Content and Fatty Acid Composition of Soybean Seeds - KARAASLAN, DAVUT; BOYDAK, ERKAN; TURKOGLU, HUSEYIN; HAKAN, MEHMET (Asian Journal of Chemistry, 2010)
The effect of seed rates and cultivars on protein, oil and fatty acid composition of soybean seeds grown in Southeast Anatolia region was studied. Protein content of soybean varied from 28.95 to 36.03 % and the oil content of soybean varied from 18.23 to 20.26 %. The protein and oil contents were significantly different among treatments (p < 0.001). Seed rates affected all the treatments significantly (p < 0.001). Myristic acid varied from 0.010 to 0.033 %, palmitic acid varied from 11.1 to 14.63 %, palmitoleic acid varied from 0.16 to 0.36 %, heptadecanoic acid varied from 0.12 to 0.29 %, heptadecenoic acid varied from 0.16 to 0.33 %, stearic acid varied from 4.58 to 7.17 %, oleic acid varied from 27.40 to 30.90 %, linoleic acid varied from 41.55 to 50.33 %, linolenic acid varied from 5.18 to 8.37 %, arachidic acid varied from 0.24 to 0.52 %, gondoic acid varied from 0.21 to 0.35 %, behenic acid varied from 0.11 to 0.17 % and lignoceric acid varied from 0.01 to 0.03 %, respectively. Correlation coefficients between protein and oil content were -0.2170. Seed rates and seed rates × cultivars interaction effects were also found to be significant (p < 0.001) over the oleic and linoleic acid contents.